Screening targeted testis-specific genes for molecular assessment of aberrant sperm quality - Liu, Xue Xia; Shen, Xiao Fang; Liu, Fu-Jun (Molecular medicine reports, 2016)
Teratospermia is a heterogeneous and complex disorder, which is closely associated with male fertility. Genes and gene products associated with teratospermia may serve as targeted biomarkers that help understand the underlying mechanisms of male infertility; however, systematic information on the subject remains to be elucidated. The present study performed a comparative bioinformatics analysis to identify biomarkers associated with sperm quality, particular focusing on testis-specific biomarkers. A stepwise screening approach identified 1,085 testis/epididymis-specific genes and 3,406 teratospermia-associated genes, resulting in 348 testis-specific genes associated with aberrant sperm quality. These genes were functionally associated with the reproduction process. Gene products corresponding to heat shock protein family A (Hsp70) member 4 like (HSPA4L) and phosphoglycerate kinase 2 were characterized at the cellular level in human testes and ejaculated spermatozoa. HSPA4L expression in sperm was revealed to be associated with sperm quality. The present study provided a novel insight into the understanding of sperm quality, and a potential method for the diagnosis and assessment of sperm quality in the event of male infertility.